Trade Policy and the American Income Distribution - Hartigan, James C.; Tower, Edward (The Review of Economics and Statistics, 1982)
P REVIOUS studies of the effects of U.S. tariffs and quotas on U.S. real income and its distribution have concluded that these effects are minimal. Moreover, this conclusion has